2023
DOI: 10.3390/d15101058
|View full text |Cite
|
Sign up to set email alerts
|

A Hotspot of Subterranean Biodiversity on the Brink: Mo So Cave and the Hon Chong Karst of Vietnam

Louis Deharveng,
Cong Kiet Le,
Anne Bedos
et al.

Abstract: The southern part of the Mekong Delta Limestones of Vietnam (MDL-HC or Hon Chong karst) comprises numerous small limestone hills. It is a hotspot of biodiversity for soil and cave invertebrates. Here, we synthesize the results of biological surveys carried out in Hang Mo So, the richest MDL-HC cave for troglobionts, and in surrounding karsts. Methodologies for the ecological characterization of species are discussed, with emphasis on parallel sampling (external soil plus cave). Hang Mo So has 27 troglobionts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Lukić et al [36] reported that almost all information for the fauna of the Lukina Jama-Trojama Cave System in Croatia dates from the 1990s or later. The same is true for Fern Cave in Alabama [44], Hon Chong in Vietnam [46], and the Água Clara Cave System in Brazil [27,28]. Sampling effort is therefore a major determinant of the richness of species in these caves.…”
Section: Taxonomic Completenessmentioning
confidence: 88%
See 2 more Smart Citations
“…Lukić et al [36] reported that almost all information for the fauna of the Lukina Jama-Trojama Cave System in Croatia dates from the 1990s or later. The same is true for Fern Cave in Alabama [44], Hon Chong in Vietnam [46], and the Água Clara Cave System in Brazil [27,28]. Sampling effort is therefore a major determinant of the richness of species in these caves.…”
Section: Taxonomic Completenessmentioning
confidence: 88%
“…Deharveng et al [46] employed a decision system to determine if a species was troglobiotic in their analysis of Vietnamese caves. These caves are usually short and shallow, with frequent terrestrial and aquatic connections to the exterior, allowing constant inputs of nutrients.…”
Section: Number Of Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the HSBs are situated in temperate regions, with only a smaller portion located in sub-tropical or tropical areas [4][5][6][7][8][9][10][11]. Additionally, it is noteworthy that most HSBs within these sub-tropical and tropical regions have only recently come to the forefront, signifying an upsurge in cave fauna research in these regions.…”
mentioning
confidence: 99%